Research to policy and practice change: is capacity building in operational research delivering the goods?. Issue 9 (9th June 2014) - Zachariah, Rony; Guillerm, Nathalie; Berger, Selma; Kumar, Ajay M. V.; Satyanarayana, Srinath; Bissell, Karen; Edginton, Mary; Hinderaker, Sven Gudmund; Tayler‐Smith, Katie; Van den Bergh, Rafael; Khogali, Mohammed; Manzi, Marcel; et al.
Abstract Objectives Between 2009 and 2012, eight operational research capacity building courses were completed in Paris (3), Luxembourg (1), India (1), Nepal (1), Kenya (1) and Fiji (1). Courses had strict milestones that were subsequently adopted by the Structured Operational Research and Training InitiaTive (SORT IT) of the World Health Organization. We report on the numbers of enrolled participants who successfully completed courses, the number of papers published and their reported effect on policy and/or practice. Design Retrospective cohort study including a survey. Methods Participant selection criteria ensured that only those proposing specific programme‐related and relevant operational research questions were selected. Effects on policy and/or practice were assessed in a standardised manner by two independent reviewers. Results Of 93 enrolled participants from 31 countries (14 in Africa, 13 in Asia, two in Latin America and two in South Pacific), 83 (89%) completed their courses. A total of 96 papers were submitted to scientific journals of which 89 (93%) were published and 88 assessed for effect on policy and practice. There was a reported effect in 65 (74%) studies including changes to programme implementation (27), adaptation of monitoring tools (24) and changes to existing guidelines (20). Conclusion Three quarters of published operational research studies from these structured courses had reported effects on policy and/or practice. It is important that this type of tracking becomes a standard component of operational research and research in general.